2011
DOI: 10.1093/carcin/bgr241
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of AKT activity is associated with reversible dormancy in ascites-derived epithelial ovarian cancer spheroids

Abstract: Epithelial ovarian cancer (EOC) metastasis is a direct contributor to high recurrence and low survival for patients with this disease. Metastasis in EOC occurs by cell exfoliation from the primary tumor into the fluid-filled peritoneal cavity, persistence of these cells as non-adherent multicellular aggregates or spheroids and reattachment of spheroids to form secondary lesions. We have recovered native spheroids from ascites fluid and demonstrated that EOC cells within these structures exhibit reduced prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 45 publications
12
98
1
1
Order By: Relevance
“…Our laboratory has independent evidence that the PI3 K-AKT pathway is down-regulated endogenously during EOC spheroid formation, yet its activation is required again during spheroid reattachment and cell dispersion [28]. Taken together, AKT and BMP signalling are co-ordinately down-regulated during EOC spheroid formation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our laboratory has independent evidence that the PI3 K-AKT pathway is down-regulated endogenously during EOC spheroid formation, yet its activation is required again during spheroid reattachment and cell dispersion [28]. Taken together, AKT and BMP signalling are co-ordinately down-regulated during EOC spheroid formation.…”
Section: Discussionmentioning
confidence: 91%
“…5c). We and others have demonstrated that active PI3 KmTOR signalling is vital to promoting the metastatic potential of EOC cells and spheroids [26][27][28][29]. Indeed, treatment of reattaching primary EOC spheroids with any of three different inhibitors of the PI3 K-mTOR pathway, LY294002, rapamycin and temsirolimus (Torisel Ò ), resulted in a significant reduction in cell dispersion (Suppl.…”
Section: Bmp Signalling Activates the Akt Pathway In Eoc Cells And Sphementioning
confidence: 99%
“…Floating tumour spheroids of ovarian cancer cell lines or spheroids isolated directly from patients’ peritoneal fluid (ascites) were shown by one study to enter a G0/G1 arrest 23 . This arrest was due to AKT inhibition and increased p130 (also known as RBL2) and p27 (also known as KIP1) protein levels, which sequester RB and inhibit cyclin-dependent kinase 4 (CDK4) and/or CDK6 activity to induce G0/G1 arrest.…”
Section: Coordination Of Quiescence and Autophagymentioning
confidence: 99%
“…Quiescent D2.0R cells are induced to proliferate through b1-integrin activation of SRC and focal adhesion kinase (FAK), leading to extracellular signal-regulated kinase (ERK)-dependent myosin light chain phosphorylation by myosin light chain kinase and actin stress fiber formation. Dual signaling by fibroblast growth factor (FGF-2) which acts directly through phosphatidylinositol 3-kinase (PI3 K) and integrin a5b1 is also necessary for cortical rearrangement in dormant cells [20].…”
Section: Cellular Factors Signaling Pathways and Tumor Dormancymentioning
confidence: 99%